High-thermal-conductivity antioxidant carbon fiber as well as preparation method and application thereof
By introducing magnesium into the mesophase asphalt, high thermal conductivity and oxidation-resistant carbon fibers are prepared, which solves the problem of easy oxidation of carbon fibers at high temperatures, and achieves a comprehensive improvement of the high-temperature oxidation and performance of the material.
Patent Information
- Application Number
- CN202411872182.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-14
AI Technical Summary
High thermal conductivity carbon fiber composite materials are easily oxidized at high temperatures, resulting in the overall failure of the material and the inability to fully exert their performance.
High thermal conductivity and oxidation-resistant carbon fibers are prepared by introducing magnesium into the mesophase bitumen and magnesium-based mesophase bitumen as a precursor. Magnesium reacts with carbon to form magnesium carbide, isolating oxygen in the air and avoiding oxidation reactions.
It improves the oxidation resistance of carbon fiber, ensures that it is not easy to oxidize at high temperatures, extends the service life of the material, and maintains its thermal conductivity and mechanical properties.
Smart Images

Figure CN119615420A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high-performance carbon fiber preparation, and specifically relates to a high-thermal-conductivity, oxidation-resistant carbon fiber and a preparation method and application thereof. Background Art
[0002] High thermal conductivity carbon fiber has excellent properties such as high strength, high modulus, high thermal conductivity, and low thermal expansion coefficient. It is very suitable for the outer space environment with large temperature difference between day and night. It has been used in the preparation of various high temperature resistant composite materials abroad, such as structural / functional composite materials for satellite shells, satellite high-power heat sinks, and solar cell back panels for space stations. Due to its excellent performance, it also has good application prospects in the civilian market. For example, it can be used to manufacture composite crucibles for steelmaking and electrolytic aluminum. This crucible has all the advantages of traditional graphite crucibles, such as good corrosion resistance, which can protect molten steel and molten aluminum from oxygen and water in the air, thereby effectively improving the purity of steelmaking and electrolytic aluminum. Due to the excellent mechanical properties and high heat resistance of high thermal conductivity carbon fiber composite materials, it is better than traditional graphite crucibles in terms of stability under thermal shock, especially able to resist the impact of high temperature molten steel. In addition, the high thermal conductivity carbon fiber composite material has been graphitized and has good self-lubricating properties. In the process of steelmaking and electrolytic aluminum, the contact area between the crucible and molten steel and molten aluminum can be reduced, effectively reducing the wear of the crucible and extending the service life of the crucible. In addition, compared with traditional graphite crucibles, high thermal conductivity carbon fiber composite crucibles have higher thermal conductivity and electrical conductivity, which can effectively transfer heat and reduce heat loss.
[0003] However, high thermal conductivity carbon fiber composite crucibles, like graphite crucibles, have a significant disadvantage: they are easily oxidized when the temperature exceeds 400°C, which affects the life of the crucible. The existing technology is to coat a layer of antioxidant components on the surface of the carbon fiber to improve the antioxidant properties of the carbon fiber composite material. When the carbon fiber in the composite material is exposed to a high-temperature oxidative atmosphere, the outer layer of the carbon fiber can achieve better anti-oxidation corrosion performance, but the inner layer of the carbon fiber is easily oxidized to produce cavities. The generation of cavities causes oxygen to further erode the inside of the carbon fiber, eventually causing the overall hollowing of the composite material, seriously affecting the life of the composite material.
[0004] Therefore, how to improve the overall antioxidant properties of carbon fiber composites and prepare a carbon fiber composite material that has excellent antioxidant properties, high thermal conductivity and mechanical properties has become a technical problem that needs to be urgently solved in the prior art. Summary of the invention
[0005] In order to solve the shortcomings of the above-mentioned prior art, the present invention provides a method for preparing high thermal conductivity and oxidation-resistant carbon fiber. The carbon fiber prepared by this method has high antioxidant capacity inside, which can solve the problem that high thermal conductivity carbon fiber is easily oxidized from the inside at high temperature and eventually causes the overall failure of the material, resulting in its performance cannot be fully exerted, and solves the application difficulty of high thermal conductivity carbon fiber composite materials under high temperature conditions.
[0006] The specific technical solutions adopted are as follows:
[0007] A method for preparing high thermal conductivity and oxidation-resistant carbon fiber comprises the following steps:
[0008] The mesophase asphalt is acidified to obtain acidified mesophase asphalt; magnesium chips are reacted with n-butyl bromide to obtain n-butyl magnesium bromide; the acidified mesophase asphalt is reacted with n-butyl magnesium bromide to obtain magnesiumized mesophase asphalt; and the magnesiumized mesophase asphalt is used to prepare high thermal conductivity and oxidation-resistant carbon fibers.
[0009] Furthermore, the specific steps of acidifying the mesophase asphalt are as follows:
[0010] Dissolve 1 to 2 parts of potassium permanganate and 1 to 2 parts of sulfuric acid in 20 to 40 parts of water to obtain a first mixed solution;
[0011] The mesophase asphalt is crushed and sieved to obtain the mesophase asphalt powder. 2 to 4 portions of the mesophase asphalt powder are added with water and stirred into a muddy state. The first mixed liquid is dripped into the mixture in portions, 25 to 100 ml each time. After each dripping, the mixture is stirred for 3 to 10 minutes and then left to stand. The color change of the liquid is observed. If the color of the liquid becomes lighter, the first mixed liquid is continued to be dripped until the color of the liquid no longer changes.
[0012] After solid-liquid separation, the solid is dried at 100-110°C to obtain the acidified mesophase asphalt. Preferably, after the liquid is extracted, the solid is washed with 400-600 mL of 5% hydrochloric acid solution, and the washing is repeated 2-3 times before the solid is dried.
[0013] The reaction principle is as follows:
[0014] PH-CH2+6KMnO4+9H2SO4→PH-COOH+3K2SO4+6MnSO4+14H2O
[0015] Further, the specific steps of reacting magnesium chips with n-butyl bromide are:
[0016] Mix 6 to 15 parts by mass of n-butyl bromide and 2.5 to 3 parts by mass of anhydrous ether to obtain a second mixed solution;
[0017] Mix 1-2 parts of magnesium chips with 2.5-3 parts of anhydrous ether, add iodine tablets, and drop 5-10 ml of the second mixed solution. After the solution is slightly boiled and the color of iodine disappears, drop the remaining second mixed solution under stirring, heat to a slight boil, stir for 15-30 minutes, then evaporate the ether to obtain n-butyl magnesium bromide.
[0018] The reaction principle is as follows:
[0019]
[0020] Furthermore, the specific steps of reacting the acidified mesophase asphalt with n-butylmagnesium bromide are:
[0021] By weight, 2 to 5 parts of acidified mesophase asphalt and 1 part of n-butylmagnesium bromide are mixed, heated to 100 to 110° C., stirred and kept at a constant temperature for 20 to 40 minutes, then heated to 130 to 135° C., and the solution is evaporated to obtain magnesium-containing mesophase asphalt.
[0022] The reaction principle is as follows:
[0023] PH-COOH+C4H9MgBRr→RH-C(=O)OMgBr+C4H 10
[0024] Furthermore, the specific steps of using the magnesium-containing mesophase pitch to prepare high thermal conductivity and oxidation-resistant carbon fibers are as follows:
[0025] The magnesium-containing mesophase asphalt is sequentially subjected to spinning treatment, oxidation treatment, carbonization treatment and graphitization treatment to obtain high thermal conductivity and oxidation-resistant carbon fiber.
[0026] The invention also discloses a high thermal conductivity and oxidation-resistant carbon fiber, which is characterized by thermal conductivity ≥600W / (m·K), tensile strength ≥2500MPa, tensile modulus ≥800GPa, elongation ≥0.80%, and ablation rate ≤0.010% at 400°C for 1 hour.
[0027] Furthermore, the high thermal conductivity and oxidation-resistant carbon fiber is prepared by any of the above-mentioned preparation methods. Preferably, the thermal conductivity is ≥795W / (m·K), the tensile strength is ≥2855MPa, the tensile modulus is ≥876GPa, the elongation is ≥0.84%, and the ablation rate at 400℃ for 1 hour is ≤0.000%.
[0028] The present invention also discloses the application of any of the above-mentioned high thermal conductivity and oxidation-resistant carbon fibers in the field of high temperature resistant composite materials.
[0029] Furthermore, it is used to prepare aerospace materials, or to prepare composite material crucibles.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention discloses for the first time a method for preparing high thermal conductivity and anti-oxidation carbon fibers by introducing magnesium into mesophase asphalt and using magnesium-containing mesophase asphalt as a precursor. The present invention introduces magnesium as an anti-oxidation component into the mesophase asphalt molecule. During the high-temperature reaction, magnesium reacts with carbon to generate magnesium carbide with a melting point of up to 2300°C. Under high temperature conditions, it can effectively isolate oxygen in the air and prevent oxidation reaction between oxygen and carbon fibers. The carbon fibers prepared using the precursor have anti-oxidation capabilities both inside and outside, and can be used as excellent reinforcements for high-temperature anti-oxidation composite materials. It has practical significance for improving the thermal oxidation resistance of composite materials and increasing service life. In addition, since magnesium is evenly distributed inside the carbon fibers in an atomic state, it can correct defects such as cracks and voids inside the carbon fibers during high-temperature reactions, thereby ensuring the thermal conductivity and mechanical properties of the high thermal conductivity carbon fibers, and thus ensuring the various properties of the carbon fiber composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a SEM picture of the high thermal conductivity and oxidation resistant carbon fiber manufactured by the present invention heated in a high temperature oven at 400° C. for 1 hour.
[0033] Figure 2 This is the SEM image of ordinary high thermal conductivity carbon fiber heated in a high-temperature oven at 400°C for 1 hour. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is clearly and completely described below in conjunction with specific embodiments. It should be pointed out that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect.
[0035] The raw materials used in the examples of the present invention and the comparative examples are as follows. Unless otherwise specified, the raw materials used in the examples of the present invention are common commercially available products.
[0036] The product performance testing methods of the embodiments of the present invention and the comparative examples are as follows:
[0037] The thermal conductivity of the carbon fibers prepared in the examples and comparative examples was tested using a LF467 thermal conductivity meter, using the standard GB / T22588-2008 "Flash method for measuring thermal diffusion coefficient or thermal conductivity";
[0038] The elongation and mechanical properties testing is based on GB / T 31290-2022 Determination of tensile properties of carbon fiber monofilament.
[0039] The antioxidant performance index is tested by measuring the mass loss rate of the fiber after heating it in an oven at 400°C for 1 hour.
[0040] Example 1
[0041] This embodiment provides a method for preparing high thermal conductivity and oxidation-resistant carbon fiber, comprising the following steps:
[0042] (1) Acidification of mesophase asphalt:
[0043] Dissolve 50g potassium permanganate and 50g sulfuric acid in 1000ml pure water, crush the mesophase asphalt and sieve it with a 1000-mesh stainless steel mesh, take 100g of the filtered mesophase asphalt powder and place it in a beaker with stirring, add 100ml pure water and stir to make the mesophase asphalt muddy, then drip the above-mentioned potassium permanganate and sulfuric acid mixture in batches, 50ml each time, stir for 5 minutes and then stand, observe the color of the liquid, if the color becomes lighter, drip the mixture again until the color no longer changes. Draw out the liquid in the beaker, rinse the inside of the beaker with 500ml of 5% hydrochloric acid, repeat 3 times and dry at 105℃ to obtain the acidified mesophase asphalt.
[0044] (2) Preparation of n-butylmagnesium bromide:
[0045] First, mix 30 ml of n-butyl bromide and 20 ml of anhydrous ether for later use. Then, place 8 g of magnesium chips, 20 mL of anhydrous ether and a small iodine tablet in a stirred flask. Drop 5-10 ml of the mixture into the flask. After the solution boils slightly and the color of iodine disappears, start stirring and slowly drop the remaining mixture into the flask. Heat the flask to a slight boil and evaporate the excess ether after stirring for 20 minutes. This is n-butyl magnesium bromide.
[0046] (3) Magnesiumization of mesophase pitch:
[0047] Mix 2 parts by weight of acidified mesophase pitch and 1 part by weight of n-butylmagnesium bromide, heat to 100°C, stir and keep constant temperature for 30 minutes, then heat to 130°C, evaporate the solution, and the remainder is magnesium-containing mesophase pitch.
[0048] (4) Preparation of high thermal conductivity carbon fiber:
[0049] The magnesium-containing mesophase asphalt is spun, oxidized, carbonized and graphitized to obtain high thermal conductivity and oxidation-resistant carbon fibers.
[0050] The performance test results of the high thermal conductivity and oxidation-resistant carbon fibers prepared in this embodiment are shown in Table 1. Figure 1 This is a SEM image of the high thermal conductivity and oxidation-resistant carbon fiber prepared in this example heated in a high-temperature oven at 400°C for 1 hour.
[0051] Example 2
[0052] The difference between this embodiment and embodiment 1 is that:
[0053] (1) Acidification of mesophase asphalt: 100 g of sulfuric acid and 200 g of mesophase asphalt powder;
[0054] (2) Preparation of n-butylmagnesium bromide: Take 25 ml of n-butyl bromide and 5 g of magnesium chips;
[0055] (3) Magnesiation of mesophase pitch: 3 parts by weight of acidified mesophase pitch and 1 part by weight of n-butylmagnesium bromide were mixed, heated to 110° C., stirred and kept at constant temperature for 30 min, then heated to 135° C. and the solution was evaporated;
[0056] The rest is completely consistent with Example 1.
[0057] The performance test results of the high thermal conductivity and oxidation-resistant carbon fibers prepared in this embodiment are shown in Table 1.
[0058] Example 3
[0059] The difference between this embodiment and embodiment 1 is that:
[0060] (1) Acidification of mesophase asphalt: 75 g of sulfuric acid and 150 g of mesophase asphalt powder;
[0061] (2) Preparation of n-butylmagnesium bromide: Take 35 ml of n-butyl bromide and 10 g of magnesium chips;
[0062] (3) Magnesiation of mesophase pitch: 4 parts by weight of acidified mesophase pitch and 1 part by weight of n-butylmagnesium bromide were mixed, heated to 100°C, stirred and kept at constant temperature for 30 minutes, then heated to 135°C and the solution was evaporated;
[0063] The rest is completely consistent with Example 1.
[0064] The performance test results of the high thermal conductivity and oxidation-resistant carbon fibers prepared in this embodiment are shown in Table 1.
[0065] Example 4
[0066] The difference between this embodiment and embodiment 1 is that:
[0067] (1) Acidification of mesophase asphalt: 60 g of sulfuric acid and 100 g of mesophase asphalt powder;
[0068] (2) Preparation of n-butylmagnesium bromide: Take 50 ml of n-butyl bromide and 5 g of magnesium chips;
[0069] (3) Magnesiation of mesophase pitch: 5 parts by weight of acidified mesophase pitch and 1 part by weight of n-butylmagnesium bromide were mixed;
[0070] The rest is completely consistent with Example 1.
[0071] The performance test results of the high thermal conductivity and oxidation-resistant carbon fibers prepared in this embodiment are shown in Table 1.
[0072] Comparative Example 1
[0073] The mesophase pitch was directly spun, oxidized, carbonized and graphitized to obtain high thermal conductivity carbon fiber. The ablation rate, thermal conductivity and mechanical properties before and after the ablation experiment were measured.
[0074] The performance of Comparative Example 1 before ablation is as follows:
[0075] Thermal conductivity 850 W / (m·K), tensile strength 3055 MPa, tensile modulus 850 GPa, elongation 0.92%.
[0076] The performance test results of the high thermal conductivity carbon fiber before and after ablation of Comparative Example 1 are shown in Table 1. Figure 2 This is an SEM image of the high thermal conductivity and oxidation-resistant carbon fiber prepared in this comparative example heated in a high-temperature oven at 400°C for 1 hour.
[0077] Comparative Example 2
[0078] 1% nano-MgO powder by mass of the mesophase asphalt was added to the mesophase asphalt, and the mixture was evenly mixed, spun, oxidized, carbonized and graphitized to obtain carbon fiber. The performance test results of the high thermal conductivity and oxidation-resistant carbon fiber prepared in this comparative example are shown in Table 1.
[0079] Comparative Example 3
[0080] Nano-MgO powder accounting for 5% of the mass of the mesophase asphalt was added to the mesophase asphalt, and the carbon fiber was obtained by spinning, oxidation, carbonization and graphitization after mixing. The performance test results of the high thermal conductivity and oxidation-resistant carbon fiber prepared in this comparative example are shown in Table 1.
[0081] Comparative Example 4
[0082] Nano-MgO powder accounting for 10% of the mass of the mesophase asphalt was added to the mesophase asphalt, and the carbon fiber was obtained by spinning, oxidation, carbonization and graphitization after mixing. The performance test results of the high thermal conductivity and oxidation-resistant carbon fiber prepared in this comparative example are shown in Table 1.
[0083] Table 1 Performance test results of high thermal conductivity and oxidation resistant carbon fibers of the embodiments and comparative examples
[0084]
[0085]
[0086] It can be seen from Table 1 that the comprehensive performance of the high thermal conductivity and anti-oxidation carbon fiber prepared by the preparation method of the present invention is better, and it can be seen from the lateral comparison between Examples 1 to 4 that in step (3), with the increase of the acidified asphalt content, although the thermal conductivity is improved, the ablation resistance gradually decreases, and the tensile strength also gradually decreases. This is because as the ablation of the fiber increases, the fiber surface is damaged, resulting in a decrease in tensile strength. Therefore, in order to ensure the comprehensive performance of the high thermal conductivity and anti-oxidation carbon fiber, the preferred mass ratio of the acidified intermediate phase asphalt to n-butyl magnesium bromide is 2 to 5:1. In addition, by adopting the method of introducing magnesium element of the present invention, magnesium exists in the fiber in an atomic manner and is evenly distributed, thereby improving the thermal conductivity of the fiber.
[0087] It can be seen from Comparative Example 1 that the performance of untreated high thermal conductivity carbon fiber is excellent at low temperature. Although the thermal conductivity of the carbon fiber monofilament does not change much at high temperature, the overall thermal conductivity of the composite material relying on carbon fiber thermal conduction will decrease due to severe ablation, and the mechanical properties will decrease significantly.
[0088] It can be seen from Comparative Examples 2 to 4 that although the ablation resistance is improved by introducing magnesium elements by adding different contents of MgO into the intermediate phase asphalt, the actual microscopic distribution of MgO in the carbon fiber is not uniform due to the physical stirring method, resulting in uneven ablation of the carbon fiber. In addition, as the MgO content increases, it leads to uneven aggregation of MgO, which destroys the internal structure of the carbon fiber, and thus various performances are greatly reduced.
[0089] It can be seen from the above embodiments and comparative examples that the Mg in the high thermal conductivity and oxidation-resistant carbon fiber of the present invention is evenly distributed in the carbon fiber, and the content requirements of the required reagents in each reaction process are not strict. It has a good inheritance and development of various properties of the carbon fiber, and the ratio of each reagent can be adjusted according to different needs, which is suitable for large-scale promotion.
Claims
1. A method for preparing high thermal conductivity and oxidation-resistant carbon fiber, characterized in that: The steps include: Acidifying the mesophase pitch to obtain acidified mesophase pitch; reacting the acidified mesophase pitch with n-butylmagnesium bromide to obtain magnesium-containing mesophase pitch; The magnesium-containing mesophase asphalt is used to prepare high thermal conductivity and oxidation-resistant carbon fibers.
2. The preparation method according to claim 1, characterized in that: The specific steps of acidifying the mesophase asphalt are as follows: Dissolve 1 to 2 parts of potassium permanganate and 1 to 2 parts of sulfuric acid in 20 to 40 parts of water to obtain a first mixed solution; The mesophase asphalt is crushed and sieved to obtain the mesophase asphalt powder. 2 to 4 portions of the mesophase asphalt powder are added with water and stirred into a muddy state. The first mixed liquid is dripped into the mixture in portions, 25 to 100 ml each time. After each dripping, the mixture is stirred for 3 to 10 minutes and then left to stand. The color change of the liquid is observed. If the color of the liquid becomes lighter, the first mixed liquid is continued to be dripped until the color of the liquid no longer changes. After solid-liquid separation, the solid is dried at 100-110°C to obtain the acidified mesophase asphalt.
3. The preparation method according to claim 1, characterized in that: The n-butyl magnesium bromide is obtained by reacting magnesium chips with n-butyl bromide, and the specific steps are: Mix 6 to 15 parts by mass of n-butyl bromide and 2.5 to 3 parts by mass of anhydrous ether to obtain a second mixed solution; Mix 1-2 parts of magnesium chips with 2.5-3 parts of anhydrous ether, add iodine tablets, and drop 5-10 ml of the second mixed solution. After the solution is slightly boiled and the color of iodine disappears, drop the remaining second mixed solution under stirring, heat to a slight boil, stir for 15-30 minutes, then evaporate the ether to obtain n-butyl magnesium bromide.
4. The preparation method according to claim 1, characterized in that: The specific steps of reacting the acidified mesophase pitch with n-butylmagnesium bromide are: By weight, 2 to 5 parts of acidified mesophase asphalt and 1 part of n-butylmagnesium bromide are mixed, heated to 100 to 110° C., stirred and kept at a constant temperature for 20 to 40 minutes, then heated to 130 to 135° C., and the solution is evaporated to obtain magnesium-containing mesophase asphalt.
5. The preparation method according to claim 1, characterized in that: The specific steps of preparing high thermal conductivity and oxidation-resistant carbon fibers using the magnesium-containing mesophase pitch are as follows: The magnesium-containing mesophase asphalt is sequentially subjected to spinning treatment, oxidation treatment, carbonization treatment and graphitization treatment to obtain high thermal conductivity and oxidation-resistant carbon fiber.
6. A high thermal conductivity and oxidation resistant carbon fiber, characterized in that: Ablation rate at 400℃ for 1 hour ≤0.010%, thermal conductivity ≥600W / (m·K), tensile strength ≥2500MPa, tensile modulus ≥800GPa, elongation ≥0.80%.
7. The high thermal conductivity and oxidation resistant carbon fiber according to claim 6, characterized in that: The preparation is carried out by the preparation method described in any one of claims 1 to 5.
8. The high thermal conductivity and oxidation resistant carbon fiber according to claim 7, characterized in that: Thermal conductivity ≥795W / (m·K), tensile strength ≥2855MPa, tensile modulus ≥876GPa, elongation ≥0.84%, ablation rate at 400℃ for 1 hour ≤0.000%.
9. Use of the high thermal conductivity and oxidation-resistant carbon fiber according to any one of claims 7 to 9 in the field of high temperature resistant composite materials.
10. The use according to claim 9, characterized in that: Used to prepare aerospace materials, or used to prepare composite material crucibles.